Pengaruh Kepuasan Kerja dan Semangat Kerja terhadap Produktivitas Kerja Karyawan PT. Pos Indonesia (Persero) Baturaja - Rr Dimas Veronica Priharti; Dinda Latifa Latifa (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The effect of job satisfaction and morale on employee work productivity at PT. Pos Indonesia (Persia) Baturaja. The purpose of this study was to determine the effect of job satisfaction and morale on the work productivity of public transport employees. Pos Indonesia (Persia) Baturaja. The data analysis technique used is multiple linear regression. Based on the results of the sub-analysis of job satisfaction and morale affect the work productivity of PT. Pos Indonesia (Persero) Baturaja with t values ​​of 3.652 and 2.896. Meanwhile, it was found that job satisfaction and morale had an impact on the work productivity of PT. Pos Indonesia (Persia) Baturaja. The limitations of this study are the number of respondents who are only 30 people, as well as the results of the information obtained from the questionnaire which sometimes shows different thoughts and understandings. This study aims to provide information about the effect of job satisfaction and morale on the work productivity of public transport employees. Pos Indonesia (Persia) Baturaja